2001
DOI: 10.1177/152715440100200402
|View full text |Cite
|
Sign up to set email alerts
|

An International Perspective on Hospital Nurses’ Work Environments: The Case for Reform

Abstract: The current nursing shortage, high hospital-nurse job dissatisfaction, and reports of uneven quality of hospital care are not uniquely American phenomena. This article presents reports from 43,000 nurses at more than 700 hospitals in the United States, Canada, England, Scotland, and Germany during 1998 and 1999. Nurses in countries with distinctly different health care systems report similar shortcomings in their work environments and the quality of hospital care. Although nurse and physician competence and nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 22 publications
1
44
0
3
Order By: Relevance
“…In addition, Atashzadeh Shooride et al (2012) noted the necessity of establishing continuous supportive relationships among nurses and patients, as problematic relationships with patients and unawareness of their needs can cause moral tensions in nurses (20). Besides the significance of nurse-patient relationship, as shown in the present study, other studies have also noted the significance of a healthy relationship among the staff, as well as staff and authorities (21,22). In fact, an effective relationship is the key to patient satisfaction, cooperation, and recovery (23).…”
Section: Discussionsupporting
confidence: 75%
“…In addition, Atashzadeh Shooride et al (2012) noted the necessity of establishing continuous supportive relationships among nurses and patients, as problematic relationships with patients and unawareness of their needs can cause moral tensions in nurses (20). Besides the significance of nurse-patient relationship, as shown in the present study, other studies have also noted the significance of a healthy relationship among the staff, as well as staff and authorities (21,22). In fact, an effective relationship is the key to patient satisfaction, cooperation, and recovery (23).…”
Section: Discussionsupporting
confidence: 75%
“…This shortage is partly due to emigration of nurses but also the result of low wages, heavy workloads, poor working and living conditions, lack of resources, limited career opportunities, poor management of health services, unstable work environments and economic instability, and the impact of HIV and AIDS (Bateman 2005;Buchan 2006). Previous research reported that professional nurses feel emotionally overloaded, stressed, fatigued, helpless, hopeless, angry, shocked, grieved, irritated, fearful, unsettled, frustrated, and were experiencing job dissatisfaction, moral distress and lack of personal accomplishment -and for these reasons often left the profession (Aiken, Clarke & Sloane 2001;Pillay 2009;Shisana et al 2004;Smit 2004;Van den Berg et al 2006).…”
Section: Introduction Problem Statementmentioning
confidence: 99%
“…A recent five country study (Canada, Germany, Scotland, UK, US) involving 43,000 nursing staff, illustrates the magnitude of the problem (Aiken, et al, 2001). Nurses indicating dissatisfaction in their present jobs were: US, forty-one percent; Scotland, thirty-eight percent; England, thirty-six percent; Canada, thirty-three percent; and Germany, seventeen percent.…”
Section: Introductionmentioning
confidence: 99%